Endoscopic Measurement of Polyp Size Using a Novel Calibrated Hood - Keiichiro Kume; Tatsuyuki Watanabe; Ichiro Yoshikawa; Masaru Harada (Gastroenterology Research and Practice)
Background. Although the size of colon polyps is an important risk factor for colorectal cancer, a standardized measurement technique has yet to be determined. In clinical practice, most endoscopists estimate polyp size by uncertain visual estimation; however, colonoscopic polypectomy is indicated for adenomatous polyps more than 5 mm in diameter. We have therefore developed a novel calibrated hood that enables accurate measurement of polyp size during colonoscopy. Method. We compared prepolypectomy estimates using the calibrated hood against measurements of preformalin-fixed samples immediately after polypectomy. Results. Sixty-five polyps removed from 44 patients were included in the present study. The mean size of polyps was significantly larger at prepolypectomy (6.06 ± 1.23 mm) than after polypectomy (5.48 ± 1.31 mm, P<0.05). Conclusion. Accurately measuring the size of polyps during colonoscopy is important, since polyps are shrunk by polypectomy. Attaching the calibrated hood appears useful in the measurement of polyp size to determine indications for polypectomy in patients with colon polyps.